Distinct Gene Expression Profiles in Viable Hepatocellular Carcinoma Treated With Liver-Directed Therapy - Núñez, Kelley G.; Sandow, Tyler; Lakey, Meredith A.; Fort, Daniel; Cohen, Ari J.; Thevenot, Paul T. (Frontiers in Oncology, 2022)
Background: Hepatocellular carcinoma is a heterogeneous tumor that accumulates mutational burden and dysregulated signaling pathways that differ from early to advanced stage. Liver transplant candidates with early-stage HCC undergo liver-directed therapy (LDT) to delay disease progression and serve as a bridge to liver transplantation (LT). Unfortunately, >80% of LDT-treated patients have viable HCC in the explant liver, dramatically increasing recurrence risk. Understanding the effect of LDT on early-stage HCC could help identify therapeutic targets to promote complete pathologic necrosis and improve recurrence-free survival. In this study, transcriptomic data from viable HCC in LDT-treated bridged to transplant patients were investigated to understand how treatment may affect tumor signaling pathways. Methods: Multiplex transcriptomic gene analysis was performed from with mRNA extracted from viable tumors from of HCC patients bridged to transplant using LDT. The NanoString nCounter® Tumor Signaling 360 panel was used that containing contained 780 genes from 48 pathways involved in tumor biology and within the microenvironment as well as antitumoral immune responses was used. Results: Hierarchical clustering separated tumors into three subtypes (HCC-1, HCC-2, and HCC-3) each with distinct differences in anti-tumoral signaling and immune infiltration within the tumor microenvironment. Immune infiltration (neutrophils, T cells, and macrophages) were all lowest in subtype HCC-3. The tumor inflammatory signature consisting of 18 genes associated with PD-1/PD-L1 inhibition, antigen presentation, chemokine secretion, and adaptive immune responses was highest in subtype HCC-1 and lowest in HCC-3. History of decompensation and etiology were associated with HCC subtype favoring downregulations in inflammation and immune infiltration with upregulation of lipid metabolism. Gene expression among intrahepatic lesions was remarkably similar with >85% of genes expressed in both lesions. Genes differentially expressed (<8 genes per patient) in multifocal disease were all upregulated in LDT-treated tumors from pathways involving epithelial mesenchymal transition, extracellular matrix remodeling, and/or inflammation favoring potentially implicating intrahepatic metastases. Conclusion: Incomplete response to LDT may drive expression patterns that inhibit an effective anti-tumoral response through immune exclusion and induce intrahepatic spread.